Organizational, Systems, and Contingency Theories in Environmentally-Based Education: A Case Study in Islamic Higher Education Institutions - Ansori, Ahmad Faisol; Subandi; Syarifudin, Encep; Makbuloh, Deden (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study explores the integration of organizational, systems, and contingency theories in managing environmentally-based education at Universitas Islam Negeri Raden Intan Lampung, Indonesia. These theories provide complementary perspectives on understanding organizational dynamics and effective management strategies. Organizational theory focuses on human behavior within organizations and the influence of structure, leadership, and culture on overall performance. Systems theory highlights the interconnectivity of organizational components and their synergistic contributions to achieving collective goals. Contingency theory emphasizes adaptive management tailored to specific situational factors, such as size, complexity, technology, and environmental conditions. Using a qualitative descriptive-analytical approach, data were gathered through document analysis, semi-structured interviews, and participant observation over six months. The findings indicate that integrating these three theories enhances institutional adaptability and responsiveness, ensuring sustainable educational practices aligned with environmental challenges. This integrative approach underscores the importance of tailoring management strategies to institutional and cultural contexts, contributing to both theoretical understanding and practical application in environmentally-based educational management. The study concludes that a holistic and adaptive management framework, combining organizational, systems, and contingency theories, is essential for fostering sustainable education and maintaining institutional effectiveness amidst dynamic global challenges.